ORIENTASI DAN MANAJEMEN PENDIDIKAN ISLAM KAJIAN IHSAN: RELEVANSI KONSEP KHOSYAH DAN MUSYAHADAH DENGAN PEAK EXPERIENCE DALAM PSIKOLOGI HUMANISTIK MASLOW - Slamet Firdaus (LP2M IAIN Syekh Nurjati Cirebon, 2012)
This research is a textual research, aimed to describe the linkage betweenconcepts khosyah (fear of Allah) and musyahadah (behavior witnessed the divine secret) in a study of the concept of ihsan and its relation with peak experience (experience crowning achievement of human needs) in the study of humanistic psychology. The method used is the thematic approach interpretation (maudlu’i) and the scientific approach interpretation (‘ilmi), and ppsychological analysis. The results showed that the demands and requirements to implement ihsan, a quality indicator of closeness to God with worship, fear (khosyah) and witnessing (musyahadah), have relevance to the findings of the study of human psychology of peak demand (peak experience) that needs toactaalization. In khosyah aspect (fear), the peak performance of human needs is to be a mature character in accordance with the core teachings of religion, fear of losing favor and always done with quality. In musyahadah aspects (see behavioral), performance peak (peak experience) lies in the spiritual sense of happiness and enjoyment, and having them ecstatic and transcendental councciousness.